Human Mental Intentionality and Microbial Growth in Cultures of Cooked Rice - Yuen, Bonny B H; Lai, Alan W L; Burchett, Richard (Journal of Scientific Exploration, 2018)
The hypothesis that microbial growth can be influenced with intention in “cultured” cooked rice was pilot tested under triple-blind conditions for 30 days. During the test, positive and negative intentions were focused towards two sets of cooked rice samples while controls received no treatments. Resulting images were taken and blindly rated by 79 judges for aesthetic perception. Results indicated that, the microbial growth observed in all “cultured” rice samples, scores of aesthetic perception on “cultured” rice samples with positive intention were higher than the controls as well as the those cultured with negative intention (p < .001), thus supporting the hypothesis.